African American female students in online collaborative learning activities: The role of identity, emotion, and peer support. (October 2016) - Du, Jianxia; Zhou, Mingming; Xu, Jianzhong; Lei, Sao San
Abstract: The aim of the present study was to explore how African American female students perceived their experience of online collaborative learning. A qualitative study was conducted in a university in Southeastern United States. We conducted semi-structured interviews with nine African American female students in an online multimedia instructional design course. Data triangulation was achieved by including the analysis of the students' emails, their posts on online chat room and bulletin boards. Results revealed that the perspectives of African American women towards online collaborative learning could be categorized into three themes: (a) peer support perceived as a give-and-take process with a sense of fairness, (b) group member role as a formation of identity, and c) "frustration" as a common response to differing levels of peer participation and interaction. These emerging factors reflected African American women's perceptions towards online collaborative learning and provided profound implications for future research and practice. Highlights: We examined African American female students' online collaborative learning. This qualitative study examined from a socio-emotional-cognitive perspective. African American women perceived peer supports as a give-and-take process. African American women viewed group member role as a formation of identity. "Frustration" was the common response to peer participation and interaction.